Adherence to a healthy lifestyle and its association with cognitive impairment in community-dwelling older adults in Shanghai - Qi, Yiqiong; Zhang, Ziwei; Fu, Xiya; Han, Peipei; Xu, Weixin; Cao, Liou; Guo, Qi (Frontiers in Public Health, 2023)
There is a growing body of recent literature linking the association of specific or multiple lifestyles with cognitive impairment, but most of these studies have been conducted in Western populations, and it is necessary to study multiple lifestyles and cognitive abilities in different populations, with the primary population of this study being a select group of community-dwelling older adults in Shanghai, China.The sample included 2390 community-dwelling Chinese participants. Their cognitive function was assessed using the Mini-Mental State Examination (MMSE). We defined a healthy lifestyle score on the basis of being non-smoking, performing ≥210 min/wk moderate/vigorousintensity physical activity, having light to moderate alcohol consumption, eating vegetables and fruits daily, having a body mass index (BMI) of 18.5 to 23.9 kg/m 2 , and having a waist-to-hip ratio (WHR) <0.90 for men and <0.85 for women, for an overall score ranging from 0 to 6.Compared with participants with ≤2 healthy lifestyle factors, the adjusted odds ratio (OR) and 95% confidence interval (CI) for participants with 4, 5, and 6 healthy lifestyle factors were 0.53 (95% CI, 0.29-0.98), 0.40 (95% CI, 0.21-0.75), and 0.36 (95% CI, 0.16-0.79), respectively. Only WHR (OR = 0.54, 95% CI = 0.37-0.78) and physical activity (OR = 0.69, 95% CI = 0.51-0.92) were associated with cognitive impairment. A healthy lifestyle correlated with overall cognition (β = 0.066, orientation (β = 0.049), language ability (β = 0.060), delayed recall (β = 0.045) and executive function (β = 0.044) (P all < 0.05).The study provides evidence on an inverse association between healthy lifestyles and cognitive impairment. We investigated whether healthy lifestyle was related to specific cognitive functions to provide a theoretical basis for accurate clinical prescription.